Disparities in Cardiovascular Disease Risk Among Hispanic Breast Cancer Survivors in a Population-Based Cohort. Issue 2 (15th February 2021) - Hu, Qingqing; Chang, Chun-Pin; Rowe, Kerry; Snyder, John; Deshmukh, Vikrant; Newman, Michael; Fraser, Alison; Smith, Ken; Gren, Lisa H; Porucznik, Christina; Stanford, Joseph B; Gaffney, David; et al.
Abstract: Background: Breast cancer is the leading cause of cancer death among Hispanic women. The aim of our study was to estimate cardiovascular disease (CVD) risk among Hispanic and non-Hispanic White (NHW) breast cancer survivors compared with their respective general population cohorts. Methods: Cohorts of 17 469 breast cancer survivors (1774 Hispanic and 15 695 NHW) in the Utah Cancer Registry diagnosed between 1997 and 2016, and 65 866 women (6209 Hispanic and 59 657 NHW) from the general population in the Utah Population Database were identified. Cox proportional hazards models were used to estimate hazard ratios (HRs) for CVD. Results: The risk of diseases of the circulatory system was higher in Hispanic than NHW breast cancer survivors 1-5 years after cancer diagnosis, in comparison with their respective general population cohorts (HRHispanic = 1.94, 99% confidence interval [CI] = 1.49 to 2.53; HNHW = 1.38, 99% CI = 1.33 to 1.43; 2-sided P heterogeneity = .01, respectively). Increased risks were observed for both Hispanic and NHW breast cancer survivors for diseases of the heart and the veins and lymphatics, compared with the general population cohorts. More than 5 years after cancer diagnosis, elevated risk of diseases of the veins and lymphatics persisted in both ethnicities. The CVD risk due to chemotherapy and hormone therapy was higher in Hispanic than NHW breast cancer survivors but did not differ for distant stage, higher baseline comorbidities, or baseline smoking. Conclusions: We observed a risk difference for diseases of the circulatory system between Hispanic and NHW breast cancer survivors compared with their respective general population cohorts but only within the first 5 years of cancer diagnosis.